Determination of Influence of Age and Regular Exercise on Blood Pressure in Males - Jayalakshmi, M. K.; Chandrashekhar, . (New Frontiers in Medicine and Medical Research Vol. 5, 2021)
Background: Both cross-sectional and longitudinal epidemiological studies have shown that sedentary life style elevates blood pressure and increased risk of hypertension and pre-hypertension among subjects with sedentary lifestyle. Sedentary life style increase the propensity to age related diseases and premature deaths. Inactivity may diminish life expectancy not only by predisposing to age related diseases but also it may influence the aging process itself by oxidative stress. Objectives: To determine the influence age and exercise on blood pressure in sedentary and non sedentary subjects. To compare the parameters between sedentary and non sedentary subjects. Methods: 100 male healthy sedentary and non-sedentary subjects in the age group of 25-55 years were selected randomly from the general population of Gadag city. Depending upon the age, subjects were divided into three groups for analysis. Blood pressure was recorded and compared between three groups. Results: Statistically significant increase in blood pressure in sedentary subjects and also in group two and three compared to group one which shows age factor is also important in developing hypertension.